2013
DOI: 10.1016/j.cell.2013.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Argonautes Promote Male Fertility and Provide a Paternal Memory of Germline Gene Expression in C. elegans

Abstract: SUMMARY During each life cycle germ cells preserve and pass on both genetic and epigenetic information. In C. elegans, the ALG-3/4 Argonaute proteins are expressed during male gametogenesis and promote male fertility. Here we show that the CSR-1 Argonaute functions with ALG-3/4 to positively regulate target genes required for spermiogenesis. Our findings suggest that ALG-3/4 functions during spermatogenesis to amplify a small-RNA signal that represents an epigenetic memory of male-specific gene expression. CSR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
275
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(293 citation statements)
references
References 60 publications
16
275
2
Order By: Relevance
“…RNAi inheritance has been implicated in trans-generational epigenetic inheritance in several species [17]. In C. elegans, exogenous and endogenous RNAi pathways require the argonaute genes rde-1 and ergo-1, respectively [18,19], although additional argonautes do exist and could be required for specific RNA inheritance events [20]. We found that, similar to the progressive fertility defects [6], the trans-generationally extended longevity of spr-5 mutant worms was independent of the main exogenous (Supplementary information, Figure S3A) and endogenous (Supplementary information, Figure S3B) RNAi pathways mediated by these argonautes.…”
Section: Transgenerational Longevity Of Spr-5(by101) Mutant Worms Is mentioning
confidence: 99%
See 1 more Smart Citation
“…RNAi inheritance has been implicated in trans-generational epigenetic inheritance in several species [17]. In C. elegans, exogenous and endogenous RNAi pathways require the argonaute genes rde-1 and ergo-1, respectively [18,19], although additional argonautes do exist and could be required for specific RNA inheritance events [20]. We found that, similar to the progressive fertility defects [6], the trans-generationally extended longevity of spr-5 mutant worms was independent of the main exogenous (Supplementary information, Figure S3A) and endogenous (Supplementary information, Figure S3B) RNAi pathways mediated by these argonautes.…”
Section: Transgenerational Longevity Of Spr-5(by101) Mutant Worms Is mentioning
confidence: 99%
“…In this paper mutant worms were backcrossed: jmjd-2(tm2966): 2 times, daf-12(m20): 3 times, rde-1(ne219): 3 times, set-17(n5017): 2-7 times, set-30(gk315): 2-8 times, damt-1(gk961032): 5 times, ergo-1(tm1860): 7 times, and eap-1(ok3432): 2-13 times. Generation 1 spr-5 mutant worms were obtained by crossing later generation (generation [10][11][12][13][14][15][16][17][18][19][20] homozygous mutant worms with WT males to obtain P0 heterozygous mutants. Individual P0 heterozygous mutants were picked to plates and allowed to lay generation 1 progeny after which the P0 heterozygous mutant genotype was confirmed by single worm PCR genotyping.…”
Section: Worm Strainsmentioning
confidence: 99%
“…In order to understand the potential molecular mechanism by which endogenous RNAi is required for pheromone sensation, we sought to identify candidate genes involved in sensory signaling that are expressed in ASI, ASJ, and ADL neurons, and exhibit a daf-d phenotype when mutated. The CSR-1 pathway has been shown to positively regulate the transcription of endogenous genes (Avgousti et al 2012;Conine et al 2013) through interactions with RNA polymerase II (Cecere et al 2014), and maintenance of a euchromatic chromatin state at target gene loci (Claycomb et al 2009;Seth et al 2013;Wedeles et al 2013). Thus, we hypothesize that gene expression of CSR-1 targets required for dauer formation would be downregulated in the mut-16 and csr-1 hypomorph strains, resulting in their observed daf-d phenotype.…”
Section: Csr-1 Promotes Expression Of G Proteins Required For Dauer Fmentioning
confidence: 99%
“…While the aforementioned studies utilized the powerful context of transgenes to illustrate a role for CSR-1 in opposing the piRNA pathway to promote gene expression, Conine, et al 28 provided evidence that the CSR-1 pathway is involved in transmitting a heritable memory of paternal gene expression established in sperm by the ALG-3/4 small RNA pathway. Previous work had demonstrated that ALG-3/4 associate with 26G-RNAs to regulate the expression of transcripts important for male fertility and spermatogenesis.…”
Section: Multiple C Elegans Argonautes Promote the Expression Of Spementioning
confidence: 99%
“…While rare, small RNA pathways have previously been linked to promoting the expression of targeted loci in mammalian cell culture, through mechanisms that remain largely unclear. 25 Together, these observations set the stage for three papers published in late 2013, Seth, et al, 26 Wedeles, et al, 27 and Conine, et al, 28 which demonstrated a role for the AGO, CSR-1, in promoting the expression of germline transcripts.…”
Section: Introductionmentioning
confidence: 99%